Islamization of Science and the Application of Axiology Related to the Science of Naquib Al-Attas Perspective - Arsita, Wina; Dewi, Eva; Febriza, Selsa Ihza (LPPPIPublishing, 2024)
Since its inception, the concept of Islamization of science has attracted the attention of many scholars to discuss. Muslim scholars who support this idea argue that science needs to be reintegrated with Islamic values. This is due to the view that current science has been influenced by western ideologies and philosophies that are contrary to Islamic teachings. Syed Muhammad Naquib Al-Attas is one of the main figures who consistently promotes this idea. He seeks to return science to its axiological framework, namely as a means that is not only oriented towards material progress, but also to moral and spiritual benefits. According to him, science that develops without the guidance of religious values risks bringing damage, rather than benefit, to humanity.